API5-Hsp20 axis regulate apoptosis and viral infection in mud crab (Scylla paramamosain) - Hu, Hang; Deng, Nan; Zhao, Xinshan; Yi, Cheng; Wei, Weiqian; Gong, Yi (Frontiers in Microbiology, 2023)
Apoptosis Inhibitor 5 (API5) is a widely concerned nuclear protein with diverse functions in organisms, so far, study of API5 is still quite limited in lower animals, and its role in viral immune response has not been addressed. Here, we explored the function of API5 in mud crab (Scylla paramamosain) during White Spot Syndrome Virus (WSSV) infection, the results showed that API5 was upregulated along with virus infection, silencing of API5 led to increased WSSV copy numbers and apoptotic rate of hemocytes, highlighting its significance in the immune response. Moreover, we discovered a novel interaction between API5 and Heat Shock Protein 20 (Hsp20), and then revealed that Hsp20 could promote cell apoptosis of hemocytes and reduce viral copy numbers by suppressing API5. The current study therefore improves the knowledge of API5-Hsp20 axis and provides novel insights into intricate mechanisms governing the antiviral response in marine crustaceans.